D-galactosamine/lipopolysaccharide-induced hepatotoxicity downregulates sirtuin 1 in rat liver: role of sirtuin 1 modulation in hepatoprotection - Kemelo, M K; Wojnarová, Lenka; Kutinová-Canová, Nikolína; Farghali, Hassan (Physiological research, 2014)
D-Galactosamine/Lipopolysaccharide (D-GalN/LPS) is a well known model of hepatotoxicity that closely resembles acute liver failure (ALF) seen clinically. The role of sirtuin 1 in this model has not yet been documented. However, there have been a number of studies about the cytoprotective effects of resveratrol, a SIRT1 activator, in the liver. This study was aimed at elucidating the roles of SIRT1 protein expression or catalytic activity in D-GalN/LPS model of hepatotoxicity. ALF was induced in male Wistar rats by intraperitoneal injection of D-GalN and LPS. Some groups of animals were pretreated with resveratrol and/or EX-527 (SIRT1 inhibitor). The effects of these treatments were evaluated by biochemical and Western blot studies. D-GalN/LPS treatment was able to induce hepatotoxicity and significantly increase all markers of liver damage and lipid peroxidation. A dramatic decrease of SIRT1 levels in response to D-GalN/LPS treatment was also documented. Resveratrol pretreatment attenuated D-GalN/LPS-induced hepatotoxicity. EX-527 blocked the cytoprotective effects of resveratrol. However, both resveratrol and EX-527 pretreatments did not exhibit any significant effect on SIRT1 protein expression. Collectively, these results suggest that downregulation of SIRT1 expression is involved in the cytotoxic effects of D-GalN/LPS model and SIRT1 activity contributes to the cytoprotective effects of resveratrol in the liver.
Keywords: Liver; Carbazoles; Animals; Sirtuin 1; Antioxidants; lipopolysacharidy; Rats, Wistar; Galactosamine; játra; karbazoly; lékové postižení jater; Enzyme Inhibitors; stilbeny; Stilbenes; Lipopolysaccharides; peroxidace lipidů; galaktosamin; cytoprotekce; Down-Regulation; Lipid Peroxidation; Male; modely nemocí na zvířatech; inhibitory enzymů; antioxidancia; Disease Models, Animal; Cytoprotection; Chemical and Drug Induced Liver Injury; down regulace; zvířata; mužské pohlaví; sirtuin 1; potkani Wistar